Climate Change, Peace, and Language Usage in the United Nations Reports within the ASEAN Style of Multilateralism - Ratih Dwiyani Adiputri (Universitas Djuanda, 2023)
This paper focuses on Indonesia's efforts to tackle peace-related climate change, which shows the ASEAN style of multilateralism. The multilateralism style of this Southeast Asian Regional Organization (ASEAN) highlights passivity and ineffective collaboration in the area. By studying the United Nations General Assembly plenary sessions between 2016 and 2021 and the formal documents from both the ASEAN and the Indonesian government, the paper shows that commitment to the discussion at the global and international levels is not moved beyond the meetings or implemented at the local (country) level. With such normative terminologies used in the documents and the employment of its language usage, Southeast Asian multilateralism shows the practice of upholding principles/norms in discussing climate change, but not as an outcome or action. As climate crisis action is immediately needed, one possible way can be to start by using strong words to tackle climate crises in global commitments and start to act.